Influence of the occupant factor on the thermal quality of a high energy performance house type 80 eco-bat housing, Blida program, Algeria - Ferradji, Kenza; Djaghrouri, Djamila; Benabbas, Moussadek (Technium Social Sciences Journal, 2022)
This paper discusses the best way of energy management. It is an initiation for the improvement of the constructive system in Algeria. Within the framework of the ECO-BAT program, we take a unit from the 80 HEP housing units in Blida as a case study, on which we undertake in-situ measurements and the questionnaire for a subjective evaluation of the thermal environment of the dwellings and the level of awareness among the occupants. This work aims to test the feasibility of the energy solutions adopted for this system by verifying the winter thermal comfort as well as the energy consumed for heating. The solutions of this research will be the support of improvement recommendations for energy management programs in the future.